ANALYSIS OF CORPORATE GOVERNANCE IN PREDICTING THE PERFORMANCE OF LQ45 COMPANIES - Frandy Melvin Walean; Fanny Soewignyo (SEAN Institute, 2023)
The aim of the research is to analyze the predictive ability of corporate governance on company performance. The research uses a sample of companies listed on the Indonesia Stock Exchange and listed consistently in the LQ 45 index from 2019 to 2021. Five hypotheses are tested using multiple regression analysis. The results of this research show that the greater the number of members of the board of directors, the higher the level of profitability as measured using the company's return on equity. Second, the greater the proportion of independent commissioners on the board of commissioners, the worse the company's performance as measured using return on equity. The results of this research show that a large number of directors has a positive impact on increasing the profitability of LQ45 Company. On the other hand, it was found that the greater number of independent commissioners on the board of commissioners had a negative impact on the company's level of profitability. These results can be of concern to the board of commissioners to pay attention to their role as commissioners. For regulators, determining the number of independent commissioners must be reconsidered if they cannot make a positive contribution to improving the company's performance.